Optimization of ceramic waste filter for bathroom greywater treatment using central composite design (CCD) - Mohamed, Radin; Abdulrahman, Adeleke; Sainudin, Muhammad Shabery bin; Bakar, Siti Asmah; Mohd Kassim, Amir Hashim; Al-Gheethi, Adel (ScienceDirect, 2018)
The present study aims to develop a filtration system consisting of ceramic wastes as a treatment process of bathroom greywater to reduce chemical oxygen demand (COD), Total suspended solids (TSS), Total nitrogen (TN), and turbidity. Optimization of the reduction efficiency was investigated using response surface methodology (RSM) as a function of the ceramic practical sizes (0.25–1.18 mm) and hydraulic retention time HRT (1–3 h). The functional groups on the surface of the ceramic filter media were determined using Fourier transform irradiation (FTIR), while the scanning electron microscope (SEM) was used to determine the microstructure and the surface morphology of the ceramic particles. Results revealed that the optimal reduction of COD, TSS, TN, and turbidity was influenced by active sites of the filter media (C]C, C]O, CeOeH, and OH−) and was achieved under the operating conditions of 0.25 mm of ceramic particles after 3 h of HRT, the observed and predicted reduction for COD, TSS, TN, and Turbidity were 38.8 vs. 39.8%; 58.47 vs. 59.59%; 66.66 vs. 67.32%; 88.31 vs. 89.02%, respectively. It can be concluded that the effectiveness of the ceramic filter media is a potential source for the filtration of bathroom greywater.